Decoration of reduced graphene oxide with rhodium nanoparticles for the design of a sensitive electrochemical enzyme biosensor for 17 beta-estradiol - Povedano, Eloy (2017)
A novel nanocomposite material consisting of reduced graphene oxide/Rh nanoparticles was prepared by a one-pot reaction process. The strategy involved the simultaneous reduction of RhCl3 and graphene oxide with NaBH4 and the in situ deposition of the metal nanoparticles on the 2D carbon nanomaterial planar sheets. Glassy carbon electrode coated with this nanocomposite was employed as nanostructured support for the cross-linking of the enzyme laccase with glutaraldehyde to construct a voltammperometric biosensor for 17 beta-estradiol in the 0.9-11 pM range. The biosensor showed excellent analytical performance with high sensitivity of 25.7 A mu M-1 cm(-1), a very low detection limit of 0.54 pM and high selectivity. The biosensor was applied to the rapid and successful determination of the hormone in spiked synthetic and real human urine samples. (C) 2016 Elsevier B.V. All rights reserved.